Harnessing Phosphocompost Extracts to Mitigate Meloidogyne javanica Impacts on Tomato - El Mehdi Bouchtaoui; Ayoub Haouas; Mouna Fahr; Aouatif Benali; Abdelfattah A. Dababat; Ayoob Obaid Alfalahi; Khalid Khfif; Abdelmjid Zouahri; Driss Iraqi; Khalid Azim; Abdelaziz Smouni; Fouad Mokrini (Agriculture)
This study evaluated the chemical properties of phosphocompost extracts and their effectiveness in inducing tomato seedlings resistance to Meloidogyne javanica. Phosphocomposts: Sugar beet phosphocompost (PC-SB: CP2), green waste phosphocompost (PC-GW: CP3), and olive mill waste phosphocompost (PC-OMW: CP4), were utilized to produce compost water extracts at concentrations of 1:5, 1:10, 1:20, and 1:100 g:mL and then applied as soil drenches for tomato seedlings one-week post-inoculation. The CP2 extract applied at a 1:5 dilution led to marked improvements in growth parameters, with plant height increasing by over 52.2%, shoot fresh biomass rising by approximately 52.44%, and shoot dry biomass showing a gain of 62.21%. Root biomass also rose by 33%. Chlorophyll a increased with CP4 at 1:5 and 1:100 (41.05% and 37.32%), chlorophyll b increased with CP3 at 1:5 and 1:10 (22.34% and 7.59%), while carotenes showed no variation. Polyphenols rose by 86.45–91.01% with CP2 from 1:5 to 1:20, and flavonoids increased by 64.90% with CP4 at 1:10. CP2 diminished the ultimate M. javanica population and reproduction factor by 171.43%, while CP4 at 1:20 decreased egg masses by 151.94%. The root gall index showed no variation. The chemical composition of phosphocomposts revealed that the strategic incorporation of diverse organic improvers (10%) in phosphocomposts yielded distinct nutrient signatures, with sugar beet waste enhancing PO43− (12.91 mg/L) and secondary macronutrients, green waste optimizing NO3− (69.91 mg/L) and SO42− (62.70 mg/L) availability, and olive mill waste producing superior micronutrient concentrations alongside dominant Ca (24.21 mg/L), K (392.50 mg/L), and P (9.17 mg/L) levels. Overall, the results underscore the potential of phosphocompost extracts as a viable, low-cost, and eco-friendly alternative to synthetic nematicides, offering a sustainable and resilient approach to M. javanica control while enhancing tomato plant growth.